THE IMPLEMENTATION OF VILLAGE-OWNED ENTERPRISE (BUMDES) POLICY TO IMPROVE THE VILLAGE ECONOMY IN BONE PESISIR BONE BOLANGO - Tanaiyo, Abdul Azis; Tahir, Arifin; Aneta, Yanti (Public Policy Journal, 2020)
This research aims to identify and describe (1) the implementation of village-owned enterprise (BUMDes) policy to improve the village economy in Bone Pesisir Bone Bolango and (2) the determinants of the implementation of village-owned enterprise (BUMDes) policy to improve the village economy in Bone Pesisir Bone Bolango. The research method used is qualitative. The data source of this research is primary data collected using interviews. The data analysis technique used refers to Miles and Huberman’s model. This research figures out that (1) The BUMDes policy in Bone Pesisir Bone Bolango has been well implemented, indicated by the progress of BUMDes in developing the potencies of each village. The implementation is perceived to give contributions to the village economy as the village original income (PADes) has been elevated since then. Besides, in terms of the community, the economy has been rising, thus reducing the unemployment level and poverty rate in the villages and (2) The determinants are crucial to implementing the village-owned enterprise (BUMDes) policy to elevate the village economy in Bone Pesisir Bone Bolango. With the management of BUMDes, the determinants form a harmony that the better the determinants i.e. communication, resources, and bureaucratic disposition and structure, the better the management of BUMDes. Of the four factors, two factors i.e. communication and resources are in an optimal state; while the two others i.e. the implementer’s commitment and clear job description have to join the individuals’ capacity building division and the management of BUMDes division.